Recommending marketing strategy and its role in achieving competitive advantage An exploratory search of the views of a sample of workers in the company of the Sufis Industries / Baghdad - fouad hamoudy alattar (Iraqi Journal for Administrative Sciences, 2025)
Business Organizations in the 21st century face many challenges represented in the development of information technology & in changing toward market globalization in addition to the change in customers wants & tastes . This requires determining Marketing strategies in View of contemporary Marketing concepts represented by marketing customization strategy that is all what the customer wants . Marketing is going to be reformulated according to the customers view point by changing the designs of making & marketing the products to him according to his desire . The mutter is more than that since changing in marketing practices focuses on the customer himself , making him the core of all marketing processes . this makes it necessary for organizations to adopt a developed information technology so as to set precise data bases to know the customer & determine the marketing strategies appro pirate for the production process to meet his desire & target him rightly . To full fill the aims of the study 52- item questionnaire is used investigating the opinions of a sample of employees in the general company for Wool Industries / Baghdad . It is used a main tool for data collection , in addition to the use of the balanced mean , standard deviation , response tensely , T & F tests & R2 correlative in analyzing the answers . The study reached at a number of conclusion , of which is that there is a connection & effectiveness relationship between marketing customization strategy & competitive advantage . In the light of this relationship , some recommendations are proposed in accordance with those conclusions .